Enzymová a fluorescenční analýza polysacharidů izolovaných z ječmenu: vliv plísňové infekce a rozdíly odrůd - Synytsya, Andriy; Lhotáková, Eva; Čopíková, Jana; Kvasnička, František (Chemické listy, 2010)
The aim of this work is detection of specific glucans extracted from barley grains of three varieties by the flow injection method of fluorescence analysis. The extract composition is monitored by HPLC of neutral sugars and FTIR spectrometry and improved by enzyme treatment (amylase and xylanase). The content of cereal ?-glucans in grains was determined using an enzyme set. The Aniline Blue dye and Fluorochrom (Biosupplies, Australia) were used as fluorescence agents. Both the agents show high sensitivity to ?(1›4) glycosidic bonds. Cereal ?-glucan and also ?-glucan did not form complexes. A statistically significant decrease in cereal ?-glucans was observed in infected grains. Purified extracts from infected grains showed more intense fluorescence than those from corresponding uninfected grains. This difference could be explained by the presence of mould ?-glucans. The flow injection fluorescence analysis is able to detect mouldinfected barley grains.
Keywords: fluorescenční barviva; fluorescence; Financing, Organized; Food Contamination; spektroskopie infračervená s Fourierovou transformací; Spectroscopy, Fourier Transform Infrared; ječmen (rod); financování organizované; kontaminace potravin; Hordeum; beta-glukany; Fluorescent Dyes; Fluorescence; beta-Glucans